Evidence to Action: The 10th International Conference on Typhoid and Other Invasive Salmonelloses. (15th February 2019) - Lindsay, Sarah; Garrett, Denise; Steele, Duncan
Abstract: Typhoid and other invasive salmonelloses continue to cause a significant burden of disease, including morbidity, mortality, and financial cost, in low- and middle-income countries. Prevention and control efforts for these diseases encounter challenges and require a coordinated global response. To organize this effort, share breakthrough research, and discuss innovative solutions, the Coalition Against Typhoid, based at the Sabin Vaccine Institute, convened the 10th International Conference on Typhoid and Other Invasive Salmonelloses in Kampala, Uganda, from 4–6 April 2017. Here, we review the significant topics and research discussed at the conference, including disease burden, diagnosis and detection, antimicrobial resistance, and prevention and control methods.